2016
DOI: 10.1016/j.tjog.2015.03.009
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review: What is the best first-line approach for cesarean section ectopic pregnancy?

Abstract: This systematic review aims to analyze the case reports, case series, or clinical studies describing the women with cesarean scar ectopic pregnancy (CSEP), and thus, to determine the efficacy and safety of different primary treatment modalities in the management of CSEP. A thorough search of electronic databases showed that 274 articles on CSEP were published between January 1978 and April 2014. Systemic methotrexate, uterine artery embolization, dilatation and curettage (D&C), hysterotomy, and hysteroscopy we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
92
2
27

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(129 citation statements)
references
References 33 publications
2
92
2
27
Order By: Relevance
“…3,[8][9][10] Regarding recovery time, the mean hospitalization time was 5.7 days in the present study, whereas more than 10 days are necessary for spontaneous reabsorption of the CSP sac by systematic methotrexate treatment or UAE alone. In terms of treatment efficiency, the success rates of systemic methotrexate, UAE, hysteroscopy, and dilatation have been reported as 8.7%, 18.3%, 39.1%, and 61.6%, 8 respectively, which are all lower than the 99.0% success rate observed in the present study.…”
Section: Discussionmentioning
confidence: 94%
“…3,[8][9][10] Regarding recovery time, the mean hospitalization time was 5.7 days in the present study, whereas more than 10 days are necessary for spontaneous reabsorption of the CSP sac by systematic methotrexate treatment or UAE alone. In terms of treatment efficiency, the success rates of systemic methotrexate, UAE, hysteroscopy, and dilatation have been reported as 8.7%, 18.3%, 39.1%, and 61.6%, 8 respectively, which are all lower than the 99.0% success rate observed in the present study.…”
Section: Discussionmentioning
confidence: 94%
“…Further, patients presenting with an exogenously located CSEP are ideal candidates for laparoscopic intervention [7]. In a current literature review by Kanat-Pektas et al, 274 papers were evaluated with respect to different treatment modalities [13]. Methotrexate treatment was found to be the least effective method.…”
Section: Discussionmentioning
confidence: 99%
“…In a type II CSP, the progression is toward the bladder and the abdominal cavity, and thus it poses a greater threat than a type I CSP. Despite this study, conservative management in general is fraught with danger and the use of systemic MTX may not be as successful as in tubal ectopic pregnancies [7]. Sugawara et al [8] reported three cases of CSP that were successfully managed by UAE and direct injection of MTX to the gestational mass and surrounding myometrium.…”
mentioning
confidence: 85%